KAJIAN PENERIMAAN DAN PENGGUNAAN CORELDRAW UNTUK PEMBELAJARAN MULTIMEDIA - RAHMATIKA RAHMATIKA (LPPM, 2015)
The main factors that determine the success of the application of information technology in education is the aspect of user behavior (user acceptance). The willingness of users to accept or use of information technology is the key to successful application of information technology. To identify the factors that influence the acceptance and use as well as identify the relationship moderating variable on the factors that influence the acceptance and use by using the Model Unified Theory of Acceptance and Use of Technology (UTAUT). UTAUT Model identifies four factors driving acceptance as a free variable that Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Condition. In this study, the effect of added two variables, namely Anxiety and Self-efficacy. The model was tested with the modified method of path analysis (path analysis) to determine the influence caused by these variables on the acceptance of use CorelDraw for multimedia learning. Based on 175 samples taken, obtained variable results Facilitating Condition (FC) affect user acceptance. UTAUT models play an important role in determining the variables and factors that influence the acceptance and use of information technology. Keywords: User Acceptance, Model of UTAUT, CorelDraw